The acute effects of dairy calcium intake on fat metabolism during exercise and endurance exercise performance - White, K. M.; Lyle, R. M.; Flynn, M. G.; Teegarden, D.; Donkin, S. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
The purpose of this study was to test the effect of acute dairy calcium intake on exercise energy metabolism and endurance performance.Trained female runners completed two trials. Each trial consisted of a 90-min glycogen depletion run followed by a self-paced 10K time trial, conducted one hour after consumption of a high dairy (500 mg Ca+2) or low dairy (80 mg Ca+2) meal. During the 90-min run, blood samples and respiratory gases were collected. No treatment main effects of acute dairy intake were found for respiratory exchange ratio (RER), calculated fat oxidation, lactate, glycerol, or 10K time. Following this protocol, acute dairy calcium intake did not alter fat utilization or endurance performance in trained female runners.